Interneurons Regulate Locomotion Quiescence via Cyclic Adenosine Monophosphate Signaling During Stress-Induced Sleep in Caenorhabditis elegans. Issue 1 (1st September 2019) - Cianciulli, Alana; Yoslov, Lauren; Buscemi, Kristen; Sullivan, Nicole; Vance, Ryan T; Janton, Francis; Szurgot, Mary R; Buerkert, Thomas; Li, Edwin; Nelson, Matthew D
Abstract: Sleep is evolutionarily conserved, thus studying simple invertebrates such as Caenorhabditis elegans can provide mechanistic insight into sleep with single cell resolution. A conserved pathway regulating sleep across phylogeny involves cyclic adenosine monophosphate (cAMP), a ubiquitous second messenger that functions in neurons by activating protein kinase A. C. elegans sleep in response to cellular stress caused by environmental insults [stress-induced sleep (SIS)], a model for studying sleep during sickness. SIS is controlled by simple neural circuitry, thus allowing for cellular dissection of cAMP signaling during sleep. We employed a red-light activated adenylyl cyclase, IlaC22, to identify cells involved in SIS regulation. We found that pan-neuronal activation of IlaC22 disrupts SIS through mechanisms independent of the cAMP response element binding protein. Activating IlaC22 in the single DVA interneuron, the paired RIF interneurons, and in the CEPsh glia identified these cells as wake-promoting. Using a cAMP biosensor, epac1-camps, we found that cAMP is decreased in the RIF and DVA interneurons by neuropeptidergic signaling from the ALA neuron. Ectopic overexpression of sleep-promoting neuropeptides coded by flp-13 and flp-24, released from the ALA, reduced cAMP in the DVA and RIFs, respectively. Overexpression of the wake-promoting neuropeptides coded by pdf-1 increased cAMP levels in the RIFs. Using a combination of optogenetic manipulation and in vivo imaging of cAMP we have identified wake-promoting neurons downstream of the neuropeptidergic output of the ALA. Our data suggest that sleep- and wake-promoting neuropeptides signal to reduce and heighten cAMP levels during sleep, respectively.